ChemInform Abstract: Gold‐Catalyzed 1, 3‐Transposition of Ynones. Issue 7 (29th January 2015) - Kazem Shiroodi, Roohollah; Soltani, Mohammad; Gevorgyan, Vladimir
Abstract The analog of (Ie) bearing a phenyl instead of a 2‐tolyl group is shown to be less reactive providing a mixture of the regioisomeric starting material and product.